Preparation and Assessment of Surface and Functional Properties of Protein Blends from Moringa oleifera and Monodora myristica Seeds - A. E. Samuel; Y. B. Hyeladzira; S. I. Hussaina; F. Muhammad; Y. K. Adamu; N. Halliru; S. Mukhtar (Journal of Applied Sciences and Environmental Management)
Protein, an amphoteric macromolecule has proven to play important role in enhancing nutritive standard and product quality. Recently, research attention is been focused on the protein fraction implicit in underexploited biomass to address the increasing demand for this agro-based resource with exceptional attributes. Consequently, the objective of this paper was to prepare and assess the surface and functional properties of protein blends compounded from Moringa oleifera and Monodora myristica seeds using appropriate standard techniques. The protein blends showed thixotropic behavior at elevated concentration and presented 1MOI:1MMI blend with the highest values of 9.75%, 22.47%, 32.11%, 60.21% and 72.09% for polar, basic, acidic, hydrophilic and non-essential amino acid distributions respectively. In contrast, 1MOI:2MMI and 2MOI:1MMI blends showed higher essential, aliphatic, aromatic, hydrophobic and non-polar amino acid distributions albeit lower in the former. The surface tension for the protein blends is in inverse proportion with concentration, consistent with their refractive indices (1.42-1.51), ηsp (1.95-5.92 cP), ηint (128.14-257.81 cP) and EȠ (5.51-14.40 KJmol-1). The protein blends exhibited foaming and solubility properties which were dependent on pH, whereas their swelling characters were influenced by temperature. The 1MOI:1MMI and 2MOI:1MMI polypeptide blends showed better emulsifying properties and surface hydrophobicity respectively. Based on the surface and functional characteristics of these biopolymer blends, they could find application as suitable hydrocolloids for food, pharmaceutical and allied industrial products.